APLIKASI GAYA BELAJAR PADA KEGIATAN BELAJAR MANDIRI MAHASISWA TAHUN PERTAMA FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH MAKASSAR - , UMMU KALZUM MALIK, dr. Ova Emilia, Ph.D, Sp.OG(K). ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background. Information of learning styles is needed by the student. At the time of self-learning, students have the freedom to be able to identify learning needs to be spelled out in the form of learning objectives, and then prepare a lesson plan, look for the resources needed to learn and implement the plan as well as the end of the evaluation results and the learning process. In this learning process learning styles can be a catalyst for effective learning. There are many styles of learning, one of which is the Visual, Aural, Read / write, Kinesthetic (VARK). This study would like to see the application of learning style of first-year students at the Faculty of Medicine, University of Muhammadiyah Makassar by the time they learn to be independent. Method. This study was a descriptive study with a quantitative approach. The population was freshman of FK Unismuh in school year 2013/2014. The data were taken in two phases. The first phase by distributing questionnaires to obtain VARK learning styles of students. The second phase, which follows the first stage students were given self-learning diary filled according to what they do during independent study. The data were analyzed descriptively. Results. Based on the analysis of data obtained unimodalitas student's learning style were Visual 1.4%, 29% Aural, Read / write 24.6%, Kinesthetic 32%, and 13% multimodality. Of group unimodalitas only 10% who applied learning style according to the characteristics of learning styles while multimodality group at 77.7%. Conclusion. The results of this study shows that the most dominant learning style in the first-year students FK Unismuh is kinesthetic learning style but group learning style multimodality most widely applied learning style according to the learning style characteristics